Immunotherapy for nonsmall cell lung cancer: a new therapeutic algorithm. Issue 2 (6th February 2020) - Berghmans, Thierry; Dingemans, Anne-Marie; Hendriks, Lizza E.L.; Cadranel, Jacques
After a nihilistic period lasting for decades, major progress in nonsmall cell lung cancer (NSCLC) therapy were linked to the introduction of platinum-based regimens, third generation chemotherapeutic drugs and, more recently, with the discovery of oncogenic driver mutations and the development of very effective targeted therapies [1]. However, for a long time, despite known significant immune dysregulations in the lung cancer environment, clinical trials with immune therapy failed to be superior to standard therapy. Adjuvant vaccination was one of the most recent prominent failures [2]. Immunotherapy is a new approach for the treatment of lung cancer with impressive long-term results http://bit.ly/35GVzAn